Revisiting Liberty of Woman Under Rape Laws in India with Reference to Bhartiya Nyaya Sanhita: A Critical Legal Analysis - Manjari Singh; Ridwan Arifin; Varun Chhachhar; Marina Gorbatiuc; Shobhit Pratap Singh; Prashant Singh (Unnes Law Journal, 2026)
Rape was clearly defined as an offence in the Indian Penal Code of 1860, drafted by the First Law Commission. For over a century, criminal laws relating to rape cases remained unchanged until the Mathura Custodial Rape Case prompted the Criminal Law (Second Amendment) Act of 1983. Subsequent legislative responses followed major cases, the 2012 Delhi Rape Case led to the Criminal Law (Amendment) Act, 2013, which provided for the death penalty in rape cases in which the death of the victim is caused or she is left in a vegetative state; the Unnao Rape Case of 2017 precipitated the Criminal Law (Amendment) Act, 2018, which made the punishment more strict and inserted several provisions; and in July 2024, new criminal laws were enforced. Despite these successive legislative interventions, each considered revolutionary in its time, heinous incidents have continued unabated, from the Hyderabad Rape Case of 2019 and the Hathras Rape Case of 2020 to the Kolkata Rape Case of August 2024. The cases from Mathura custodial rape to Kolkata rape have witnessed no change in the mentality of the society, which revolves around gender injustice and questions the physical appearance of a girl/woman. This paper analyses the rape laws through a critical examination of the after-effects of the 2013 and 2018 amendments of old criminal laws and the provisions of new criminal laws. It also traces the evolving meaning of the "personal liberty" of women across this period. The analysis reveals that deterrent laws have become a necessity, yet their implementation in society remains ineffective. The core cause behind these recurring cases lies not merely in legislative gaps but in deeply entrenched social attitudes that successive amendments have failed to address. Legislative reform alone cannot deliver justice when societal mentality remains unchanged. This paper employs a doctrinal-analytical method, drawing on constitutional provisions, statutory texts, Supreme Court jurisprudence, parliamentary committee reports, and National Crime Records Bureau data to critically examine the legislative and judicial treatment of rape law in India. This paper criticizes the gap between law on paper and law in action, underscoring that the personal liberty of women demands not only stronger legal frameworks but their meaningful and consistent enforcement.